2011
DOI: 10.1007/s00262-010-0963-5
|View full text |Cite
|
Sign up to set email alerts
|

Targeting NKT cells and PD-L1 pathway results in augmented anti-tumor responses in a melanoma model

Abstract: Invariant or Type 1 NKT cells (iNKT cells) are a unique population of lymphocytes that share characteristics of T cells and natural killer (NK) cells. Various studies have shown that positive costimulatory pathways such as the CD28 and CD40 pathways can influence the expansion and cytokine production by iNKT cells. However, little is understood about the regulation of iNKT cells by negative costimulatory pathways. Here, we show that in vivo activation with α-GalCer results in increased cytokine production and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 43 publications
(50 reference statements)
3
39
0
Order By: Relevance
“…While literature contains conflicting data about iNKT anergy, multiple studies reported that the PD-1/PD-L1 checkpoint pathway plays a critical role in regulation of iNKT cell activity. 42,57,61 When investigating the involvement of this checkpoint axis in the present study, we confirmed the up-regulation of PD-1 in activated NKT cells, as well as its ligand PD-L1 in APCs in the systemic organs ( Figure 5 and Figure S9). We could also detect a pronounced PD-L1 expression in tumors of nanoparticle-treated animals.…”
Section: Galsomessupporting
confidence: 81%
“…While literature contains conflicting data about iNKT anergy, multiple studies reported that the PD-1/PD-L1 checkpoint pathway plays a critical role in regulation of iNKT cell activity. 42,57,61 When investigating the involvement of this checkpoint axis in the present study, we confirmed the up-regulation of PD-1 in activated NKT cells, as well as its ligand PD-L1 in APCs in the systemic organs ( Figure 5 and Figure S9). We could also detect a pronounced PD-L1 expression in tumors of nanoparticle-treated animals.…”
Section: Galsomessupporting
confidence: 81%
“…Interestingly, the B7-CD28 co-stimulatory pathway can modulate development of NKT cells [57,58] and PD-1/PD-L1 interaction is essential for the induction and maintenance of iNKT cell anergy. PD-1/PD-L blockade prevents anergy induction and enhances the anti-tumor activities of glycolipid-activated invariant NKT cells in the melanoma model [59]. We detected an increase in PD-1 expression on NK and NKT cells; however, it did not lead to augmented expansion of NKT cells in healthy B7-H1KO mice.…”
Section: Discussionmentioning
confidence: 86%
“…Administration of aGC is known to induce iNKT cell anergy by triggering the upregulation of PD-1 on iNKT cells (48). We and others have previously demonstrated that blocking the PD-1/PD-L1 interaction can prevent anergy induction in iNKT cells and enhance the antitumor effects of iNKT cells (48)(49)(50). In advanced tumors, NK cells also express Tim-3 and PD-1 and become functionally exhausted (31).…”
Section: Discussionmentioning
confidence: 99%